Identification of a founder EPCAM deletion in Spanish Lynch syndrome families. (26th April 2013) - Mur, P.; Pineda, M.; Romero, A.; del Valle, J.; Borràs, E.; Canal, A.; Navarro, M.; Brunet, J.; Rueda, D.; Ramón y Cajal, T.; Lázaro, C.; Caldés, T.; et al.
<x xml:space="preserve">Abstract</x> Germline deletions at the 3′‐end of EPCAM have been involved in the etiology of Lynch syndrome (LS). The aim of this study was to characterize at the molecular level Spanish families harboring EPCAM deletions. Non‐commercial multiplex ligation‐dependent probe amplification (MLPA) probes and long‐range polymerase chain reaction (PCR) amplification were used to characterize each deletion. Haplotyping was performed by analyzing eight microsatellite markers and five MSH2single nucleotide polymorphisms (SNPs). Methylation of MSH2 was analyzed by methylation specific‐MLPA. Tumors diagnosed in seven Spanish families harboring EPCAM deletions were almost exclusively colorectal. Mosaicism in MSH2 methylation was observed in EPCAM deletion carrier samples, being average methylation levels higher in normal colon and colorectal tumors (27.6% and 31.1%), than in lymphocytes and oral mucosa (1.1% and 0.7%). Three families shared the deletion c.858 + 2568_*4596del, with a common haplotype comprising 9.9 Mb. In two families the novel EPCAM deletion c.858 + 2488_*7469del was identified. This study provides knowledge on the clinical and molecular characteristics of mosaic MSH2 epimutations. The identification of an EPCAM founder mutation has useful implications for the molecular diagnosis of LS in Spain.